The World robot summit disaster robotics category – achievements of the 2018 preliminary competition. (2nd September 2019) - Tadokoro, Satoshi; Kimura, Tetsuya; Okugawa, Masayuki; Oogane, Katsuji; Igarashi, Hiroki; Ohtsubo, Yoshikazu; Sato, Noritaka; Shimizu, Masaru; Suzuki, Soichiro; Takahashi, Tomoichi; Nakaoka, Shin'ichiro; Murata, Mika; et al.
Abstract : The World Robot Summit is a robot Olympics and aims to be held in a different country every four years from 2020. The concept of the Plant Disaster Prevention challenge is daily inspections, checks, and emergency response in industrial plants, and in this competition, robots must carry out these types of missions in a mock-up plant. The concept of the Tunnel Disaster Response and Recovery challenge is emergency response to tunnel disasters, and is a simulation competition whereby teams compete to show their ability to deal with disasters, by collecting information and removing debris. The Standard Disaster Robotics challenge assesses, in the form of a contest, the standard performance levels of a robot that are necessary for disaster prevention and emergency response. The World Robot Summit Preliminary Competition was held at Tokyo Big Sight in October 2018, and 36 teams participated in the Disaster Robotics Category. UGVs and UAVs contended the merits of new technology for solving complex problems, using core technologies such as mobility, sensing, recognition, performing operations, human interface, autonomous intelligence etc., as well as system integration and implementation of strategies for completing missions, gaining high-level results. GRAPHICAL ABSTRACT: